PENGGUNAAN METODE PEMBIASAAN DALAM MEMBENTUK KARAKTER DISIPLIN ANAK USIA 5-6 TAHUN DI PAUD SARTIKA ASIH MEKARMULYA - Nurhayati, Ida; Hidayat, Rahmat; Hidayat, Yusuf (Jurnal Intisabi, 2024)
As an effort to form the qualified generation, character education must be instilled as early as possible through habituation. This study aims to determine the use of habituation method in forming discipline character to early childhood aged 5-6 years at Kober Sartika Asih Mekarmulya. The method used in this study is a Classroom Action Research (CAR). The study was carried out through 2 cycles, at which each cycle refers to four components: planning, acting, observing, and reflexing. The results of the study showed that the use of the habituation method in the cycle I asserted an average score of 70% in the formation of early childhood’s discipline character with a distribution of 17 early childhoods achieving the completeness of Beginning to Develop (MB) and 15 early childhoods achieving the completeness of Developing as Expected (BSH). Then, after improvements were made in cycle II, there was an increase on the average score of early childhood’s discipline character reaching 84% with the distribution of 13 early childhoods achieving the completeness of Developing as Expected (BSH) and 19 early childhoods achieving the completeness of Developing Very Good (BSB). In conclusion, the use of habituation method has a significant effect on the formation of early childhood’s discipline character at PAUD Sartika Asih Mekarmulya.